Europe and the Caribbean : threat or opportunity. - Thorndike, Tony (1990)
Traces the importance of Europe to the Caribbean in the context of the 'Americanization' of the Region. Examines the mechanisms by which the region could exploit the latent opportunities represented by the new Europe. Reviews the options open to the region so far as Europe and North America are concerned.